Training and Placement Android Application - Shaikh, SM; Ganbavale, AS; Gaikwad, SP; Bhujbal, MR; Aldar, KM (International Journal of Computer Sciences and Engineering, 2025)
the existing work of training & placement in Sanjay Ghodawat Institute (SGI) is fully manual process and due to this manual process, management faces many problems for collecting student details. The aim of this project is Automation of Training and Placement unit of SGI, Atigre. The project will include minimum manual work and maximum optimization, abstraction and security. This is an android application which will help students and Training and Placement Officer (TPO) to carry out every placement related activity. The system can be accessed throughout the SGI organization with proper login. It is used by the TPO to manage the student’s information and fast access in placement related activities such as applying for drive. Students logging should be able to upload their information. The key feature of this project is that it has a decision Forum, where queries asked by students can be solved by higher authorities. Students will get notified when TPO’s upload study material or any campus drive information, through this system. Automatic Training and placement is developed to maintain the details of student information, trace the details of student also maintain the information about the company availability.